An application of conjugate gradient method under strong Wolfe line search for solving unconstrained optimization - Khadijah, Wan; Rivaie, Mohd; Mamat, Mustafa; Hajar, Nurul; ‘Aini, Nurul; Zainal Abidin, Zubai’ah (International Journal of Engineering and Technology, 2018)
The conjugate gradient (CG) method is one of the most prominent methods for solving linear and nonlinear problems in optimization. In this paper, we propose a CG method with sufficient descent property under strong Wolfe line search. The proposed CG method is then applied to solve systems of linear equations. The numerical results obtained from the tests are evaluated based on number iteration and CPU time and then analyzed through performance profile. In order to examine its efficiency, the performance of our CG formula is compared to that of other CG methods. The results show that the proposed CG formula has better performance than the other tested CG methods.